16 Extra- and Intraoperative Electrocortical Stimulation (Pediatric Epilepsy Surgery, 2019)
Electrocortical stimulation (ECS) is still the gold standard for defining functional cortex when planning a focal resection to treat medically refractory epilepsy. While it is a valuable tool used at all level IV epilepsy surgery centers, it requires in depth knowledge and experience of specific pediatric issues. In this chapter we will review the current principles, practices, and techniques published from various centers, the underlying electrophysiology, pediatric stimulation paradigms and safety issues. The value of extraoperative vs. intraoperative ECS is discussed. We also review in detail the impact that developmental or acquired pathology may have on the functional anatomy of the developing brain, which is highly relevant for surgical resective planning. Electric stimulation of motor, sensory, language, and more specific cortical areas is reviewed in detail. Lastly, we discuss the value of newer noninvasive techniques as adjunctive methods for ECS that may reduce the risks of invasiveness.
Keywords: cortical; electrocortical stimulation; cortical mapping; extraoperative stimulation; intraoperative simulation